G45(P) A quality improvement project to develop an emergency neonatal intubation flowchart. (May 2019) - Jackson, S; Higgins, C; Cummins, D; McNaughten, B; Walker, A
Abstract : Introduction: If in a neonatal emergency, intubation is indicated, it is imperative the correct equipment is collected promptly to allow swift intubation. Incorrect equipment collection delays intubation, and can hinder administration of resuscitation medications and optimal oxygenation and ventilation. Currently no neonatal intubation equipment guide exists. This study aimed to develop a Neonatal Intubation Flowchart (NIF) and test its effectiveness. Methodology: A prototype NIF was created (NIF 1). Using simulation, a control group (n=21) was compared to an intervention group (n=24), utilising NIF 1. These cohorts consisted of paediatricians, neonatal nurses and midwives. The outcomes measured were Percentage of Correct Equipment (PCE) collected and Time Duration (TD) to collect equipment. Post simulation surveys with 31 participants, and focus interviews with 8 Neonatal Consultants, were undertaken for feedback and user input. This information led to development of NIF 2. The simulation was repeated with an intervention group (n=28) utilising NIF 2. Another post simulation survey was undertaken with 28 participants and further changes led to development of NIF 3. Results: Between the control, NIF 1 and NIF 2, the PCE results were 59%, 87% and 96% respectively. The TD of the control, NIF 1 and NIF 2 showed a median of 90 s (Interquartile Range (IQR): 70.5–121.5), 140 s (IQR: 99.5–182) and 60 s (IQR: 53.5–73.5). Assimilation of surveys and focus group input showed that key partners wanted improvements to equipment content, reorganisation of layout and formatting. Of the survey participants (n=59) 100% preferred the NIF to current practice. Conclusion: A novel NIF has been successfully developed to improve preparation for emergency neonatal intubation. The NIF provides superior equipment preparation and is preferred to current practice.